Implementasi Islamic Corporate Social Responsibility PT. Semen Indonesia - Dini Alfiani Maisya; Moh. Qudsi Fauzy (Universitas Airlangga, 2016)
Corporate Social Responsibility (CSR) policy is a company duty in the form of awareness toward environment, considering they grow and develop in the midst of society which may cause externality due to their production. Corporate Social Responsibility (CSR) is a company commitment to contribute in the sustainable economic development with regard to social responsibility and emphasize to the stability of economic, social, and environment aspects.The result of this research shows that PT. Semen Indonesia has implemented Corporate Social Responsibility Policies in environment sector and conform to Islam economic provision. From some indicators, PT. Semen Indonesia has implemented Corporate Social Responsibility (CSR) with equitable and benefit principle, but from charity and mandate indicators, PT Semen Indonesia has not fully comply in term of implementation.